2009
DOI: 10.1002/pro.267
|View full text |Cite
|
Sign up to set email alerts
|

Design of high‐affinity S100‐target hybrid proteins

Abstract: S100B and S100A10 are dimeric, EF-hand proteins. S100B undergoes a calciumdependant conformational change allowing it to interact with a short contiguous sequence from the actin-capping protein CapZ (TRTK12). S100A10 does not bind calcium but is able to recruit the N-terminus of annexin A2 important for membrane fusion events, and to form larger multiprotein complexes such as that with the cation channel proteins TRPV5/6. In this work, we have designed, expressed, purified, and characterized two S100-target pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…To facilitate a stable complex, we constructed a tandem chimeric protein linking the C terminus of S100A10 to the N-terminal 15-residues of annexin A2 separated by a nine-residue tether (A10A2). Comparison of 1 H-15 N HSQC spectra shows the assembly of this chimeric A10A2 protein is very similar to that of the heterotetrameric noncovalent complex that includes S100A10 and two 14-residue annexin A2 peptides (Rezvanpour et al, 2009). A variety of in vivo and in vitro studies have shown that a small region (G5654-L5673) within the 1,000-residue C terminus of AHNAK interacts with high affinity (30 nM) with the S100A10-annexin A2 complex or A10A2 (Benaud et al, 2004;De Seranno et al, 2006;Rezvanpour et al, 2011).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To facilitate a stable complex, we constructed a tandem chimeric protein linking the C terminus of S100A10 to the N-terminal 15-residues of annexin A2 separated by a nine-residue tether (A10A2). Comparison of 1 H-15 N HSQC spectra shows the assembly of this chimeric A10A2 protein is very similar to that of the heterotetrameric noncovalent complex that includes S100A10 and two 14-residue annexin A2 peptides (Rezvanpour et al, 2009). A variety of in vivo and in vitro studies have shown that a small region (G5654-L5673) within the 1,000-residue C terminus of AHNAK interacts with high affinity (30 nM) with the S100A10-annexin A2 complex or A10A2 (Benaud et al, 2004;De Seranno et al, 2006;Rezvanpour et al, 2011).…”
Section: Resultsmentioning
confidence: 89%
“…The expression/purification of the S100A10-annexin A2 chimeric protein (A10A2) has been previously described (Rezvanpour et al, 2009). Briefly, the A10A2 protein contains residues 1-92 from rabbit S100A10 (100% amino acid sequence identity with the human protein), a nine-residue linker (93-100 that contains a tobacco-etch mosaic virus (TEV) cleavage site followed by the N-terminal 15 residues (101-115) from annexin A2.…”
Section: Experimental Procedures Protein Expression and Purificationmentioning
confidence: 99%
“…The crystal structure also allows a closer analysis of the computergenerated consensus sequence based on previous peptide-array experiments (Rezvanpour et al, 2011;Rezvanpour & Shaw, 2009). Of particular concern is that strong electron density and multiple interactions with (p11) 2 (AnxA2) 2 are observed for the first five residues of the AHNAK peptide in the crystal structure, yet the consensus sequence begins at position 6.…”
Section: Analysis Of the Consensus Sequencementioning
confidence: 99%
“…Additionally, several unique and diverse binding partners and ligands of AnxA2 have been identified, such as PCSK9 (Mayer et al, 2008), phosphatidylinositol 4,5-bisphosphate (Rescher et al, 2004), heparin , chlorotoxin (Kesavan et al, 2010) and progastrin (Singh et al, 2006). Most commonly, AnxA2 exists either as a monomer or in complex with a dimer of S100A10 (also called p11), forming a heterotetramer [(p11) 2 (AnxA2) 2 ] (Gerke & Moss, 2002;Rescher & Gerke, 2008;Rezvanpour & Shaw, 2009;Gerke & Weber, 1984). The S100 family of proteins is comprised of approximately 10 kDa proteins that contain EF-hand calciumbinding sites and generally form dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation